Implementation Of Fuzzy Logic in The Dissolved Oxygen and pH Control System to Reduce the Risk of Death of Cyprinus Carpio Fish - Setyabudi, Jinna Elvaretta Aqilah; Aisyah, Putri Yeni; Fitriyanah, Dwi Nur; Radhy, Ahmad; Pratama, I Putu Eka Widya; Wiratama, Maulana Andra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Cultivation of Cyprinus carpio, commonly known as the goldfish, in aquariums requires strict monitoring of water quality to maintain the fish's health and ensure its survival. Key parameters such as dissolved oxygen and pH greatly affect the aquatic environment, where imbalances can lead to stress or death. This study aims to design and implement a dissolved oxygen and pH control system using fuzzy logic as an alternative to traditional PID-based or rule-based systems commonly used in aquaculture. The proposed system automatically detects water conditions (LOW, NORMAL, HIGH) and activates appropriate control responses. It integrates an SEN0237 dissolved oxygen sensor, an E-201C pH sensor, aerators, dosing pumps, and an Arduino-based microcontroller. Sensor data is processed via fuzzy inference to operate actuators—either to increase oxygen levels or inject buffer solutions for pH normalization. Unlike previous studies that focus on single-parameter control or fixed-response systems, this system offers a dual-parameter adaptive control approach. Experimental validation shows that the system maintains pH at 6–7 and DO at 3–4 mg/L, with sensor accuracy exceeding 95%. Over 10 days, fish survival improved in the controlled aquarium (7/10) compared to the uncontrolled aquarium (5/10). The system demonstrates potential to reduce water quality fluctuations, offering hope for a more stable aquaculture environment. This work contributes to the application of fuzzy logic in small-scale innovative aquaculture systems, highlighting its potential advantages over conventional methods.